2015
DOI: 10.3233/jcb-15006
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase R and the metabolic syndrome

Abstract: Metabolic syndrome greatly increases the risk for developing metabolic and cardiovascular disorders and has reached epidemic proportions globally. Despite recent advances in medical science, scientific understandings on the root mechanisms of metabolic syndrome are still not fully understood, and such insufficient knowledge contributes to the relative lack of effective treatments for such diseases. Protein Kinase R (PKR) is a serine threonine kinase activated during various stress conditions. Activation of PKR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Besides dsRNA, endoplasmic reticulum (ER) stress, mechanical stress, high‐fat diet, pathogens, environmental stress, haeme limitation, cytokines (TNF‐α, IL‐1β) and irradiation also possess the ability to activate PKR . In addition, researchers have found that the PACT is a plausible cellular activator of PKR which can cause the PKR phosphorylation , while others have demonstrated that protein kinase R (PKR)‐associated protein X (RAX), murine counterpart for PACT , is accountable for the activation of PKR at cellular level, when stimulated by any extracellular stress stimuli .…”
Section: Pkr: Structure and Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides dsRNA, endoplasmic reticulum (ER) stress, mechanical stress, high‐fat diet, pathogens, environmental stress, haeme limitation, cytokines (TNF‐α, IL‐1β) and irradiation also possess the ability to activate PKR . In addition, researchers have found that the PACT is a plausible cellular activator of PKR which can cause the PKR phosphorylation , while others have demonstrated that protein kinase R (PKR)‐associated protein X (RAX), murine counterpart for PACT , is accountable for the activation of PKR at cellular level, when stimulated by any extracellular stress stimuli .…”
Section: Pkr: Structure and Functionmentioning
confidence: 99%
“…Upon activation, PKR phosphorylates several downstream substrates such as protein phosphatase 2A (PP2A) and eukaryotic translation initiation factor eIF‐2α that are involved in modulating protein synthesis . Notably, PKR is implicated in regulating various physiological and pathological functions such as cell growth, apoptosis, stress, transcription and many types of malignancies .…”
Section: Pkr: Structure and Functionmentioning
confidence: 99%
See 2 more Smart Citations